Arctic drift - Cussler, Clive; Cussler, Dirk. (New York : G.P. Putnam's Sons, 2008)
Dirk Pitt searches for a crucial element that will help reverse global warming.
Map on lining papers.
Keywords: Pitt, Dirk (Fictitious character) -- Fiction; Marine biologists -- Fiction; Global warming -- Fiction; Northwest Passage -- Fiction; Arctic regions -- Fiction; Adventure fiction